Using Toe Framework to Analyze Factors Influencing Social Media Usage by Micro, Small And Medium Enterprises - Muhammad Ardiansyah; Peni Sawitri; Sanusi (LPPM Politeknik Aceh Selatan, 2021)
This study aims to evaluate the factors that influence the use of social media in micro, small and medium enterprises. By using a mixed qualitative and quantitative approach, the study examines the influence of factors based on the TOE (Technology-Organization-Environment) Framework theory. The data collection process was carried out by means of interviews and questionnaires distributed online. From the quantitative analysis conducted on 100 samples using multiple linear regression techniques, it is known simultaneously that the factors in the context of the TOE Framework have a significant effect on the use of social media in MSMEs. In the context of technology, the factors that have a significant effect on the use of social media are the interactivity of social media and the suitability of the technology that has been previously owned. Data analysis was carried out using SPSS 25. The results of the study concluded that the suitability factor, inter-activity and entrepreneurial orientation had a significant effect on the use of social media in MSMEs.